Unraveling the Mechanism of the Persistent Photoconductivity in Organic Phototransistors - Jia, Ruofei; Wu, Xiaofeng; Deng, Wei; Zhang, Xiujuan; Huang, Liming; Niu, Kaifeng; Chi, Lifeng; Jie, Jiansheng (Advanced functional materials, 2019)
Persistent photoconductivity (PPC) in organic phototransistors provides an opportunity and broad prospects to achieve many emerging applications in optoelectronic devices. However, a fundamental understanding of PPC behavior is still a key challenge impeding its practical applications. In this study, for the first time, a mechanism for electron trapping is presented in oxygen‐induced deep levels in organic semiconductors for the clarification of PPC behavior with solid evidence. Both theoretical simulation and experimental investigation unveil that oxygen in air atmosphere plays a decisive role in determining the PPC behavior. Oxygen molecules can induce deep defect levels in the energy bandgap of organic semiconductors, which will act as deep traps for photogenerated electrons. The trapped electrons will be maintained in the traps and undergo a very slow releasing process after light illumination, thus leading to a noticeable PPC behavior for the organic phototransistors. The proposed mechanism shows good universality and can be applicable to a host of organic semiconductors for explaining the PPC behaviors. This work reveals the significant role of oxygen in PPC behavior and also provides guidelines for controlling the unique PPC behavior toward device applications. A new mechanism of electron trapping in oxygen‐induced deep levels in organic semiconductors is proposed for the clarification of persistent photoconductivity (PPC) behavior in organic phototransistors (OPTs). Oxygen molecules can induce deep defect levels in the energy bandgap of organic semiconductor, which can trap the photogenerated electrons during light illumination, thus leading to a prominent PPC behavior in OPTs.